2013
DOI: 10.1016/j.rehab.2013.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Verbal communication disorders in brain damaged post-stroke patients in Benin

Abstract: In Benin, post-stroke VCD is exceedingly common and occasions major social difficulties. Prevalence of VCD in a predominantly oral culture underscores the need for speech therapists to develop a more broadly ecological approach toward treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…We reported in a previous study that its aspect, almost essentially consisting of visual items, was well adapted to aphasic patients (predominant motor aphasia). Elaborating a battery of cognitive evaluation tests to be used in these patients was in fact our first motivation, knowing that aphasia is a very common impairment post-stroke [9]. The present study shows that the administration of the test is rarely impossible in patients with severe neurovisual disorders.…”
Section: Resultsmentioning
confidence: 72%
“…We reported in a previous study that its aspect, almost essentially consisting of visual items, was well adapted to aphasic patients (predominant motor aphasia). Elaborating a battery of cognitive evaluation tests to be used in these patients was in fact our first motivation, knowing that aphasia is a very common impairment post-stroke [9]. The present study shows that the administration of the test is rarely impossible in patients with severe neurovisual disorders.…”
Section: Resultsmentioning
confidence: 72%
“…Not all studies provided information on service provision. Many studies reported a specific need for certain rehabilitation services, but then reported the service to be either absent or inefficient, that is OT/SLT (Baatiema et al 2017c;Cockburn et al 2014;Rhoda et al 2014; SLT (Kpadonou et al 2013;Sarfo et al 2017a); OT ; clinical psychologist ; mobility devices (Chimatiro & Rhoda 2014) and specialist stroke units ). Comprehensive multidisciplinary teams (MDTs) consisting of five or more healthcare professionals were reported in five South African-based studies (Andrews & Pillay 2017;Groenewald & Rhoda 2017;Rouillard et al 2012;.…”
Section: Information About Stroke Rehabilitation Servicesmentioning
confidence: 99%
“…• Cost of care (Andrews & Pillay 2017;Birabi et al 2012;Hurst et al 2016;Natta et al 2015;Sarfo et al 2018a;). • Lack of appropriate means of transport Blixen et al 2017;Damasceno et al 2010;Natta et al 2013;Ntamo et al 2013;Rouillard et al 2012;Sarfo et al 2018a). • Poor referral channels and lack of resources (Andrews & Pillay 2017;Blixen et al 2010;Cockburn et al 2014;Natta et al 2013;).…”
Section: Barriers To Rehabilitationmentioning
confidence: 99%
See 2 more Smart Citations